Simulated sudden increase in geomagnetic activity and its effect on heart rate variability: Experimental verification of correlation studies. (August 2016) - Caswell, Joseph M.; Singh, Manraj; Persinger, Michael A.
Abstract: Previous research investigating the potential influence of geomagnetic factors on human cardiovascular state has tended to converge upon similar inferences although the results remain relatively controversial. Furthermore, previous findings have remained essentially correlational without accompanying experimental verification. An exception to this was noted for human brain activity in a previous study employing experimental simulation of sudden geomagnetic impulses in order to assess correlational results that had demonstrated a relationship between geomagnetic perturbations and neuroelectrical parameters. The present study employed the same equipment in a similar procedure in order to validate previous findings of a geomagnetic-cardiovascular dynamic with electrocardiography and heart rate variability measures. Results indicated that potential magnetic field effects on frequency components of heart rate variability tended to overlap with previous correlational studies where low frequency power and the ratio between low and high frequency components of heart rate variability appeared affected. In the present study, a significant increase in these particular parameters was noted during geomagnetic simulation compared to baseline recordings.